Experimental and Numerical Investigation on Cold-formed Steel C Back-to-Back Beams - Kimcheng Kang; Taweep Chaisomphob; Wasan Patwichaichote; Eiki Yamaguchi (Institut Teknologi Sepuluh Nopember, 2017)
Investigation on flexural behavior of cold-formed steel (CFS) C back-to-back beam has been conducted in this study. In North American Specification for the Design of Cold-Formed Steel Structural Members, there is only the information on the spacing condition of C back-to-back beam. In the present experiment, twelve C back-to-back beam specimens with different connection spacing and cross-sectional dimension were tested under four-point loading. Bolts were used for connecting two C section beams. From the experimental result, the influence of the thickness and connection spacing of the C back-to-back beams were observed. Nonlinear finite element analysis of the beam specimens are performed, and compared with experimental result. It was found that the difference in ultimate load obtained from experimental and numerical result, are less than 30 percent.